2021
DOI: 10.2478/rjim-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress markers in hospitalized patients with moderate and severe COVID-19

Abstract: Background: Clinical evidence suggests increased oxidative stress in COVID-19 patients and this worsened redox status could potentially contribute to the progression of the disease. Objectives: To investigate the oxidative stress we have measured oxidative stress parameters, namely, PAT (total antioxidant power, iron reducing) and d-ROMs (plasma peroxides). Additionally we have investigated their correlation with the most frequently used clinical parameters CRP, LDH, and NLR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
13
1
1
Order By: Relevance
“…Regarding SARS-CoV-2, an observational study showed an increase in antioxidant capacity by inducing SOD and CAT in COVID-19 patients [ 42 ]. However, this was inconsistent with other COVID-19 patients [ 43 ]. This warrants additional studies to establish the link between SARS-CoV-2 and the host antioxidant system’s activation.…”
Section: Sars-cov-2 Controls Ros Levels For Its Survivalcontrasting
confidence: 86%
“…Regarding SARS-CoV-2, an observational study showed an increase in antioxidant capacity by inducing SOD and CAT in COVID-19 patients [ 42 ]. However, this was inconsistent with other COVID-19 patients [ 43 ]. This warrants additional studies to establish the link between SARS-CoV-2 and the host antioxidant system’s activation.…”
Section: Sars-cov-2 Controls Ros Levels For Its Survivalcontrasting
confidence: 86%
“…Levels of oxidative stress depend on COVID-19 severity [ 30 ] and change during the disease [ 82 ], so both factors should be considered when comparing results from different studies. Levels of superoxide anion increased substantially with increased disease severity, while hydrogen peroxide levels were similar in all hospitalized patients, independent of disease severity [ 83 ].…”
Section: Oxidative Stress and Covid-19 Severitymentioning
confidence: 99%
“…However, depending on the outcome, oxidative stress levels changed between admission and seven days after admission. In severe COVID-19 patients with fatal consequences, increased oxidative stress was observed, while in surviving patients, oxidative stress was decreased during this period [ 82 ]. Karkhanei et al found that total oxidant status increased with increased severity of COVID-19 [ 87 ].…”
Section: Oxidative Stress and Covid-19 Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, serum-free thiol concentrations have been analyzed and correlated with the disease severity: hospitalized subjects had significantly lower levels of serum-free thiols compared to non-hospitalized subjects and healthy controls (van Eijk et al, 2021). Lastly, oxidative damage to lipids has also been detected in plasma samples from patients at admission (Zendelovska et al, 2021). Indeed, physiological serum levels of 7-ketocholesterol and 7-hydroxycholesterol in SARS-CoV-2 positive subjects were significantly increased compared to healthy subjects (Marcello et al, 2020).…”
Section: Oxidative Stress-related Mechanisms In Sars-cov-2 Infections...mentioning
confidence: 99%